EFFECTIVENESS OF SCHOOL OPERATIONAL ASSISTANCE (BOS) MANAGEMENT IN MTS ALKHAIRAAT GORONTALO CITY - Olii, Rara Ayudyah; Aneta, Asna; Sulila, Ismet (Public Policy Journal, 2021)
This research confers the description of the effectiveness of School Operational Assistance (BOS) management in MTs Alkhairaat Gorontalo City and proponent and inhibiting factors. It used a qualitative descriptive approach. The research data sources were primary and secondary, collected with observation, interview, and documentation. The data analysis technique used was Miles and Huberman’s interactive analysis model. Findings demonstrate that (1) Because of its success, the School Operational Assistance program implemented in MTs Alkhairaat Gorontalo City was considered effective, (2) BOS management was ineffective, attested by stagnant students’ academic and non-academic achievements, (3) In general, the satisfaction level with the BOS program was effective, justified by parents’ responses arguing their satisfaction, (4) Input and output levels were still ineffective for there were many challenges which should be confronted to attain the program aims and targets, and (5) A successful BOS program implementation had a direct impact on the community, which now found it easy to fulfill education for children. Additionally, it is foreseeable that BOS can elevate students’ achievement in MTs Alkhairaat Gorontalo City.